Free nutritious meal program and healthy eating behavior: The mediating roles of knowledge and awareness - Masdar, Rinaldi; Taiyeb, A. Mushawwir; Jamaluddin, Asham Bin; Daud, Firdaus; Syamsiah (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
The Free Nutritious Meal Program (FNMP), known in Indonesia as Makan Bergizi Gratis (MBG), is a government initiative designed to improve students' nutritional status and promote healthy eating behavior. However, evidence regarding how the program influences students’ eating behavior remains limited. This study examined the effect of FNMP implementation on healthy eating behavior, digestive system knowledge, and nutritional awareness, as well as the mediating roles of knowledge and awareness. A cross-sectional survey was conducted among 622 eleventh-grade students from five public senior high schools in Makassar, Indonesia, selected through multistage sampling. Data were collected using questionnaires and multiple-choice tests and subsequently analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that the FNMP implementation had a significant positive effect on healthy eating behavior (β = 0.089, p = 0.043). However, the FNMP implementation did not significantly affect digestive system knowledge or nutritional awareness. Consequently, neither variable mediated the relationship between FNMP implementation and healthy eating behavior. These findings indicate that the FNMP directly improves healthy eating behavior through school-based interventions. Integrating nutrition education into the program may strengthen its effectiveness in promoting sustainable healthy eating practices among students.